The Influence of Macroeconomic Indicators on the Profitability of PT Pelabuhan Indonesia - Riansyah, Arif; Shabrina, Riyanna (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research was conducted to examine the influence of macroeconomic indicators, including the inflation rate, most-favorable nation (MFN) weighted average tariff, net trade goods (NTG), average crude oil price, and exchange rate (IDR to USD), on the profitability of ports in Indonesia represented by PT Pelabuhan Indonesia (Pelindo). Several quantitative tests were performed using secondary data from financial reports and macroeconomic data published by Pelindo and the World Bank from 2008 to 2021. The results revealed that there is a significant direct negative relationship between net trade goods and the exchange rate. However, there is no direct relationship found between the inflation rate, the most-favorable nation's (MFN) weighted average tariff, and the average crude oil price. This research is expected to benefit the government, researchers, academics, and the wider public as a literature reference for further research and to establish profitability strategies that involve macroeconomics.